2013
DOI: 10.1111/tpj.12336
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomes of isolated Oryza sativa gametes characterized by deep sequencing: evidence for distinct sex‐dependent chromatin and epigenetic states before fertilization

Abstract: SUMMARYThe formation of a zygote by the fusion of egg and sperm involves the two gametic transcriptomes. In flowering plants, the embryo sac embedded within the ovule contains the egg cell, whereas the pollen grain contains two sperm cells inside a supporting vegetative cell. The difficulties of collecting isolated gametes and consequent low recovery of RNA have restricted in-depth analysis of gametic transcriptomes in flowering plants. We isolated living egg cells, sperm cells and pollen vegetative cells from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
133
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(148 citation statements)
references
References 69 publications
10
133
0
1
Order By: Relevance
“…This finding might explain the strongly condensed, compact sperm cell chromatin (see also Figure 1A). Indeed, a similar observation was reported for rice sperm cells (Russell et al, 2012;Anderson et al, 2013). Notably, no chromatin gene is among the TOP80 genes in maize egg cells.…”
Section: Comparison Of Transcriptomic Data From Maize and Rice Gametessupporting
confidence: 77%
See 2 more Smart Citations
“…This finding might explain the strongly condensed, compact sperm cell chromatin (see also Figure 1A). Indeed, a similar observation was reported for rice sperm cells (Russell et al, 2012;Anderson et al, 2013). Notably, no chromatin gene is among the TOP80 genes in maize egg cells.…”
Section: Comparison Of Transcriptomic Data From Maize and Rice Gametessupporting
confidence: 77%
“…We used published RNA-seq data from rice sperm and egg cells (Anderson et al, 2013) and initially identified the rice homologs using public databases, i.e., EnsemblPlants and RiceAnnotationGenomeProject, which combine data from many species to identify putative orthologs. If the identity of the homologs/ orthologs was unclear or unknown due to a lack of sequence information, we did not include them in the comparison.…”
Section: Comparison Of Transcriptomic Data From Maize and Rice Gametesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, transcriptome studies of isolated sperm cells showed that sperm cells contain thousands of transcripts, consistent with transcriptional activity (13,30). This idea is supported by the identification of several sperm cell-specific genes, such as GEX1 and DUO1 (31,32).…”
Section: A Combination Of Sequences In the 5′ Utr And Coding Region Arementioning
confidence: 53%
“…Nevertheless, recent methodological advances have allowed the transcriptional profiling of such rare cell types by combining laserassisted microdissection or micromanipulation with microarray and/ or RNA-Seq analyses. These studies have provided novel insights into the transcriptional basis of germline specification and development (Wüest et al, 2010;Schmidt et al, 2011Schmidt et al, , 2012Schmidt et al, , 2014Okada et al, 2013;Wüest et al, 2013;Abiko et al, 2013;Anderson et al, 2013;Chettoor et al, 2014).…”
Section: The Acquisition and Restriction Of Reproductive Fatementioning
confidence: 99%